Sergey Alexandrovich Khmyzov - Ukrainian association of orthopaedists-traumatologists, Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The article deals with the 50th birthday of the Head of the Division of Pathology of Vertebral Column and Joints in Childhood and the Head of the Department of Paediatric Orthopaedics, Doctor of Medical Science KhmyzovS.A.